Parent calcium-rich-food practices/perceptions are associated with calcium intake among parents and their early adolescent children - Reicks, M.; Degeneffe, D.; Ghosh, K.; Bruhn, C.; Goodell, L.; Gunther, C.; Auld, G.; Ballejos, M.; Boushey, Carol; Cluskey, M.; Misner, S.; Olson, B.; et al. (Cambridge University Press, 2012)
The study aimed to (i) segment parents of early adolescents into subgroups according to their Ca-rich-food (CRF) practices and perceptions regarding early adolescent CRF intake and (ii) determine whether Ca intake of parents and early adolescents differed by subgroup. A cross-sectional convenience sample of 509 parents and their early adolescent children completed a questionnaire in 2006–2007 to assess parent CRF practices and perceptions and to estimate parent and child Ca intakes. Self-administered questionnaires were completed in community settings or homes across nine US states. Parents self-reporting as Asian, Hispanic or non-Hispanic White with a child aged 10–13 years were recruited through youth or parent events. Three parent CRF practice/perception segments were identified, including ‘Dedicated-Milk Providers/Drinkers’ (49 %), ‘Water Regulars’ (30 %) and ‘Sweet-Drink-Permissive Parents’ (23 %). Dedicated-Milk Providers/Drinkers were somewhat older and more likely to be non-Hispanic White than other groups. Ca intakes from all food sources, milk/dairy foods and milk only, and milk intakes, were higher among early adolescent children of Dedicated-Milk Providers/Drinkers compared with early adolescents of parents in other segments. Soda pop intakes were highest for early adolescents with parents in the Water Regulars group than other groups. Dedicated-Milk Providers/Drinkers scored higher on culture/tradition, health benefits and ease of use/convenience subscales and lower on a dairy/milk intolerance subscale and were more likely to report eating family dinners daily than parents in the other groups. Parent education programmes should address CRF practices/perceptions tailored to parent group to improve Ca intake of early adolescent children.